2010
DOI: 10.2478/v10045-010-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Chenopodium Ambrosioides L. (Chenopodiaceae) Products From Nigeria Against Three Storage Insects

Abstract: Toxicity ofChenopodium AmbrosioidesL. (Chenopodiaceae) Products From Nigeria Against Three Storage InsectsTests were carried out to study the toxicity, oviposition suppression, ovicidal and larvicidal effects ofChenopodium ambrosioidesL. as powder, extracts and essential oil againstCallosobruchus maculatusF. (Coleoptera: Bruchidae),Sitophilus zeamaisMotschulsky (Coleoptera: Curculionidae) andTribolium castaneumJacqueline du Val. (Coleoptera: Tenebrionidae). The powder formulation was more toxic toS. zeamaistha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 12 publications
2
16
0
5
Order By: Relevance
“…However, this species is less affected than S. zeamais for which concentrations of 8.0 and 16.0% lead to 100% mortality at 14 DAI. The reduced sensibility of T. castaneum to vegetable powders agrees with data found by Denloye et al (2010), who obtained higher mortality with extracts (LC 50 = 0.04 g L -1…”
Section: Effect Of Powder On T Castaneumsupporting
confidence: 89%
“…However, this species is less affected than S. zeamais for which concentrations of 8.0 and 16.0% lead to 100% mortality at 14 DAI. The reduced sensibility of T. castaneum to vegetable powders agrees with data found by Denloye et al (2010), who obtained higher mortality with extracts (LC 50 = 0.04 g L -1…”
Section: Effect Of Powder On T Castaneumsupporting
confidence: 89%
“…This is probably due to the possession of strong elytra that covers the entire abdomen of the insect. This confirmed earlier works by Inyang (2004), Akpabot et al(2010) and Edelduok et al (2012) who posited that coleopterans have exceptionally thick cuticles, epidermis and basement membrane as effective mechanisms of restricting toxicants absorption but disagreed with earlier work by Epidi et al (2009), Denloye et al (2010) and Udo et al(2011) who observed significant contact action on S. zeamais since they are known to be poor fliers and so were always in contact with the treated filter paper. Again, the body size of S. zeamais might enhance its efficiency in detoxifying any toxic materials in the plant product applied.…”
Section: Effect Of Cymbopogon Citratus Application On Zea Mays Grainssupporting
confidence: 75%
“…The powders were sieved using 0.5 mm size mesh. The powder was then stored in an airtight container to prevent active components from evaporating prior to used (Denloye et al, 2010).…”
Section: Collection Of Plant Materialsmentioning
confidence: 99%
“…Some studies proved efficacy of C. ambrosioides for controlling C. maculatus including toxicity to adults, reduction of oviposition, ovicidal activity and toxicity to immature stages prior to or immediately following penetration of plant tissue (Tapondjou et al, 2002;Emeasor, 2005;Denloye et al, 2010). High mortality rates obtained in this study are in accordance with the results reported by Chougourou et al, 2015, which had 100% of mortality of C. maculatus with 1.5g of C. ambrosioides per 20g of Vigna subterranea, 120 hours after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There is now renewed interest in the use of pesticides of plant origin in order to obviate the problems of environmental pollution, killing of non-target species and humans as well as reducing cost of purchasing synthetic chemical pesticides. In this context, several plants and constituent bioactive substances, also called insecticides of plant origin or botanical insecticides, have been tested and considered promising in the control of cowpea beetle (Denloye et al, 2010, Kheradmand et al, 2010, Udo, 2011. Chenopodium ambrosioides Linn and Aframomum melegueta K. Schum were chosen because they have shown promise of medicinal and insecticidal activity in Malawi, Central Africa countries such as Cameroon and Gabon and Southern Africa (Gadano, 2002, Tapondjou et al, 2002, Konning et al, 2004Okwu, 2005, Odugbemi, 2006, Denloye et al, 2009.…”
Section: Introductionmentioning
confidence: 99%